MODEL EVALUASI FORMATIF-SUMATIF TERHADAP HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN BERDIFERENSIASI PADA PESERTA DIDIK SMA - Gaspersz, Magy; AW, Suranto; Gaspersz, Netty (Prodi Magister Pendidikan Matematika Pascasarjana Universitas Pattimura Ambon, 2023)
Evaluation is a means to improve the quality of education through the results of information that is used as feedback and improvements to educational programs, one of which is the formative-summative evaluation model. This study aims to determine the effect of the formative-summative evaluation model on mathematics learning outcomes through differentiation learning in high school students. This type of research is evaluation research with a quantitative approach. Data were obtained through documentation techniques by taking samples based on certain considerations (purposive sampling), namely classes that have implemented an independent learning curriculum and educators who teach are driving educators so that planning in differentiated learning can run as expected. The results of the analysis using multiple linear regression tests obtained that there was a significant influence between the formative-summative evaluation model on mathematics learning outcomes as shown from the calculations obtained by the value of Fcount = 89.8 with a significant level of 0.05, then Ftable = 3.316 so that Fcount > Ftable or 89.8 > 3.316 then H0 is rejected. This shows that the formative-summative model can be used to evaluate student’s mathematics learning outcomes through differentiation learning